RIGHT TO SAFETY AND SECURITY FOR PASSENGERS TRAVELING BY THE PUBLIC ROAD TRANSPORTATION - Madalina, Maria; Tejomurti, Kukuh; Budyatmojo, Winarno (Yustisia, 2017)
This article aimed to observe the safety protection of public road transportation and some public areas in Yogyakarta and Surakarta. The Road and urban public transport terminals, station, and transshipment centres were mainly established at the meeting points of different traffic lines.  If we compare the terror-threat against infrastructure, building, and vehicles, then we can see that much more terrorist attacks were directed against the vehicles, than against bridges or tunnels. Safety protection on public road transportation and its  public areas is one of the efforts to enforce  right to life and right to sustain life in line with article 28A of Indonesian Constitution of 1945.  This issue is  important to be observed because two cities are prone to be attacked by terrorist and sometimes passengers or visitors are not responsive to disasters as long as they are on public road transportation and public areas.  This article have two important problem to be observed, first problem is  how already passengers  or visitors of public road transportation and its  public areas understand safety procedures of those areas?; second problem is how policy of safety protection need to be enforced on two public road transportation and public areas in order to protect right to life safely of passengers? The normative and empirical legal research is used  to this research by using interviews and field observation. The result of this research concisely state that at this time the bus station and rail  station is still not implemented maximum safety and security procedures to passengers and passengers or visitors do not understand about safety procedures and are not responsive to dangerous circumtances surrounded  them. Maximum safety protection is important to prevent  terrorism  crime, narcoticss crime, and prevent any casualties due disasters. Security officers should check the condition of bags and luggage of passengers or visitors in order to prevent any threats there. Safety briefing is also implemented to keep a passengers concer.